Inspiring improv : explore creative piecing with curves, strips, slabs and more - Ball, Nicholas (Lucky Spool Media, 2019)
Explore the freeing power of improvised piecing. Learn this step-by-step technique to explore six fundamental piecing structures. Practice how to stitch fabric together in an improvisational manner to create blocks or sections before using them to sew unique quilts all your own. Improv piecing doesn't have to mean chaotic end results. Look to the eight original projects included to see how to create sophisticated quilts with structure focusing on repeating blocks or large scale scrappy designs. Follow along as Nicholas walks you through his original inspiration and follow his plan through to finished pieces as he discusses which combination of his core piecing methods he used and how to achieve showstopping, exciting work. From simple strip piecing to complex circles and rings, you will be eager to experiment making slabs, gentle curves, insets, triangles, and even 9 patch and Log Cabin stacks, and then use them as a stepping stone to sewing original full sized designs.